Management of Complicated Crown Fracture with Miniature Pulpotomy: A case report - Asgary, Saeed; Fazlyab, Mahta (Iranian Endodontic Journal, 2014)
Crown fractures account for the majority of dental traumas If handled properly, prognosis of the pulp following a traumatic crown fracture can be favorable. The present case report focuses on the treatment of a traumatized mature permanent incisor with exposed pulp that was treated with the novel technique of miniature pulpotomy using calcium-enriched mixture (CEM) cement. One-year follow-up revealed that the tooth was responsive to vitality tests and radiographic assessment showed the presence of a thick dentinal bridge beneath the CEM layer.